Symposium on unemployment and the labor-market in ireland - introduction - Walsh, Bm (Economic & Social Studies, 1983)
One of the most controversial issues in modern labour economics surrounds the attempt to establish the existence and magnitude of the effect of unemployment insurance on the level of measured unemployment. To some economists it seems self-evident that the growth of an unemployment insurance scheme which replaces a substantial amount of the earnings lost through unemployment would have a significant effect on the level of unemployment measured in terms of applicants for unemployment benefits. Minford and Peel (1981), for example, claim that "unemployment is voluntary . . . Allowing for benefits in kind and the costs of working, a man with a wife and two children would obtain permanently in benefits a living standard about three-quarters as good as he would on average earnings" (p. 4). But it has proved difficult to obtain conclusive empirical evidence of the magnitude of this effect, so that it is possible for Atkinson (1980), for example, to conclude that "there is at present no strong evidence that there is a large proportion of volunteers among the unemployed" (p. 28).
Keywords: Economics; Sociology